Tumor evolution and drug response in patient-derived organoid models of bladder cancer - Lee, Suk Hyung (Cell, 2018)
Bladder cancer is the fifth most prevalent cancer in the U.S., yet is understudied and few laboratory models exist that reflect the biology of the human disease. Here we describe a biobank of patient-derived organoid lines that recapitulates the histopathological and molecular diversity of human bladder cancer. Organoid lines can be established efficiently from patient biopsies acquired before and after disease recurrence, and are interconvertible with orthotopic xenografts. Notably, organoid lines often retain parental tumor heterogeneity and exhibit a spectrum of genomic changes that are consistent with tumor evolution in culture. Analyses of drug response using bladder tumor organoids show partial correlations with mutational profiles as well as changes associated with treatment resistance, and specific responses can be validated using xenografts in vivo. Our studies indicate that patient-derived bladder tumor organoids represent a faithful model system for studying tumor evolution and treatment response in the context of precision cancer medicine.